2019
DOI: 10.3389/fimmu.2019.00877
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Tumor Microenvironment Alters Human NK Cell Recruitment, and Resident NK Cell Phenotype and Function

Abstract: Endometrial Cancer is the most common cancer in the female genital tract in developed countries, and with its increasing incidence due to risk factors such as aging and obesity tends to become a public health issue. However, its immune environment has been less characterized than in other tumors such as breast cancers. NK cells are cytotoxic innate lymphoid cells that are considered as a major anti-tumoral effector cell type which function is drastically altered in tumors which participates to tumor progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 57 publications
(46 reference statements)
3
93
1
Order By: Relevance
“…Moreover, a strong correlation has been observed between TIGIT expression on peripheral blood CD8 + T cells and AML relapse post‐transplantation . In endometrial cancer, high levels of TIGIT on tumour‐resident NK cells have been associated with disease severity . Finally, a high TIGIT/DNAM‐1 ratio on tumour‐infiltrating T regs was shown to correlate with poor clinical outcome following ICB targeting PD‐1 and/or CTLA‐4 .…”
Section: Tigit Inhibits Anti‐cancer Immune Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a strong correlation has been observed between TIGIT expression on peripheral blood CD8 + T cells and AML relapse post‐transplantation . In endometrial cancer, high levels of TIGIT on tumour‐resident NK cells have been associated with disease severity . Finally, a high TIGIT/DNAM‐1 ratio on tumour‐infiltrating T regs was shown to correlate with poor clinical outcome following ICB targeting PD‐1 and/or CTLA‐4 .…”
Section: Tigit Inhibits Anti‐cancer Immune Responsesmentioning
confidence: 99%
“…TIGIT up‐regulation has been observed in various malignancies, including melanoma, breast cancer, non‐small‐cell lung carcinoma (NSCLC), colon adenocarcinoma (COAD), gastric cancer, acute myeloid leukaemia (AML) and multiple myeloma (MM) . Many studies reported up‐regulated TIGIT expression on CD8 + T cells, but there are also descriptions of increased TIGIT levels on tumour‐infiltrating T regs and NK cells . In mouse pre‐clinical models and in cancer patients, TIGIT expression on tumour‐infiltrating CD8 + T cells often correlates with increased expression of other inhibitory receptors such as PD‐1, lymphocyte‐activation gene 3 (LAG‐3), T‐cell immunoglobulin and mucin‐domain containing‐3 (TIM‐3), and with decreased expression of DNAM‐1 .…”
Section: Tigit Inhibits Anti‐cancer Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, as well, blocking TIM-3 with antibodies increased NK cell cytotoxicity and cytokine secretion. Additional recent studies identified TIM-3 expression as a marker of NK cell dysfunction and disease severity in colorectal cancer, esophageal cancer, endometrial cancer, and bladder cancer (96,(98)(99)(100)(101). Interestingly, TIM-3 engagement was initially shown to increase the expression of IFN-γ by NK cells in response to galectin-9, the β-galactoside binding lectin (123).…”
Section: Tim-3mentioning
confidence: 99%
“…CXCL9 and CXCL10 are binding to CXC-chemokine receptor 3 on effector CD8 + T cells, T H 1 cells, and NK cells, thereby regulating their recruitment into tumors (Nagarsheth et al 2017). CXCL10, which is an important factor in NK cell-recruitment and NK cell-mediated lysis of tumor cells has been shown to be strongly produced in the tumor compared to the adjacent tissue, suggesting that an immune response is occurring in the tumor (Degos et al 2019). In various malignancies, CXCL9 and CXCL10 were reported to be produced predominantly by activated CD103 + dendritic cells, (tumor-associated) macrophages and tumor cells (Lieber et al 2018;Spranger et al 2017).…”
Section: Role Of Chemokines In Tumor Immunology and In Immunotherapymentioning
confidence: 99%